Study on attenuation of 3D printing commercial filaments on standard X-ray beams for dosimetry and tissue equivalence. (May 2021) - Savi, M.; Villani, D.; Andrade, M.A.B.; Rodrigues, O.; Potiens, M.P.A.
Abstract: 3D printing techniques and materials have become widely available in the last couple of decades and remains an important topic of research as the equipments and supplements gets chipper. This study aims to evaluate the attenuation behaviour of several commercially available 3D printing filaments (ABS and PLA-based filaments and other polymers blends) over standard X-ray beams ranging from 30 keV - to 50 keV and comparing the experimental results with theoretical data of Cortical Bone, Soft Tissue and PMMA. It was used the transmission method to obtain experimental attenuation coefficients to all materials. HVL for the materials were also calculated. Results show that PLA-based printing filaments mixed with metals (Al, BRASS and Cu) has higher attenuation than pure PLA. Comparing the experimental data with theoretical cross section of Soft Tissue, Cortical Bone and PMMA, it was possible to observe that with the increase of beam energy, ABS-based and other blends' attenuation behaviour agree with PMMA/Soft tissue. None of the studied materials showed agreement of attenuation with Cortical Bone. Some variations of PLA (SILK, Black and Bone) and some of the other blends of PETG and TPU showed good agreement with Soft Tissue/PMMA since about 30 keV and it can be concluded that these filaments can be used as substitute of PMMA for mimetizing soft tissue in 3D printed phantoms. Highlights: Linear attenuation coefficients of 3D printing filaments. Total Mass attenuation of 3D printing materials. PLA-based filaments more feasible for mimetizing human soft tissue.